Presence of IgE Autoantibodies Against Eosinophil Peroxidase and Eosinophil Cationic Protein in Severe Chronic Spontaneous Urticaria and Atopic Dermatitis - Sánchez, Jorge; Sánchez, Andres; Munera, Marlon; Garcia, Elizabeth; Lopez, Juan-Felipe; Velásquez-Lopera, Margarita; Cardona, Ricardo (Allergy, asthma & immunology research, 2021)
Purpose Eosinophils are frequently found in atopic dermatitis (AD) and chronic spontaneous urticaria (CSU) that release eosinophil peroxidase (EPX) and eosinophil cationic protein (ECP). Continuous exposure to these proteins could trigger an autoimmune response which may contribute to the pathogenesis and severity of skin inflammation. In this study, we investigate the immunoglobulin E (IgE) response against eosinophil proteins in CSU and AD. Methods We recruited patients with severe AD, severe CSU and healthy subjects to explore the presence of IgE autoantibodies and cross-reactivity against EPX, ECP and thyroid peroxidase (TPO). The potential cross-reactive epitopes among the peroxidase family were determined using in silico tools. Results The frequencies of anti-EPX IgE (28.8%) and anti-ECP IgE (26.6%) were higher in the AD group, and anti-TPO IgE was higher in the CSU group (27.2%). In the CSU group, there was a correlation between the anti-EPX IgE and anti-TPO IgE levels (r = 0.542, P < 0.001); TPO inhibited 42% of IgE binding to EPX, while EPX inhibited 59% of IgE binding to TPO, suggesting a cross-reactivity with EPX as a primary sensitizer. There was greater inhibition when we used a pool of sera CSU and AD, TPO inhibited 52% of IgE binding to EPX, while EPX inhibited 78% of IgE binding to TPO. In silico analysis showed a possible shared epitope in the peroxidase protein family. Conclusions IgE against eosinophil proteins may contribute to chronic inflammation in patients with AD and CSU. Cross-reactivity between EPX and TPO could explain thyroid problems in CSU patients.